Best Answer

y=6x² is already solved. the parabola will touch the x-axis at x=0.

User Avatar

Wiki User

2012-04-26 09:07:09
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
2560 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve y equals 6x squared?
Write your answer...
Still have questions?
magnify glass
Related questions

6x-18y plus 108 equals 0 solve for y?

6x +108=18y y=6x/18+108/18 y=x/3+6

How do you work out what x and y are equal to using x squared plus y squared equals 25 and y equals 3x plus 1?

since y = 3x+1 we have y squared =(3x+1) squared x^2 + y^2 = 25 x^2 + (3x+1)^2=25 x^2 + 9x^2+ 6x+1 = 25 10x^2 + 6x + 1 = 25 10x^2 + 6x -24 = 0 solve x from quadratic formula x = 1.28 y = 3x + 1 = 4.83

What is equivalent to y equals x squared-6x plus 14?

There is no non-trivial equivalent.

How do you write 6x-y equals 1?


How do you solve y equals -6xplus one?

To solve the equation for either y or x, you need to have a value for the variable you are not trying to solve for. For example, if you're solving for x in y = -6x + 1, when y = 0: 0 = -6x + 1 (substitute 0 for y) 6x = 1 (add 6x to both sides) x = 1/6 (divide both sides by 6)

Solve the system of equations 3x - 6y equals 30 y equals -6x plus 34?

x = 6 and y = -2

Solve the system of equations enter your answer as an ordered pair 6x - y equals 33 6x plus 3y equals 45?

It works out that x = 6 and y = 3 or as (6, 3)

How do you solve 6x plus 2y equals 4?

6x+2y=4 gives y=2-(1/3)x

What is slope of 6x plus 3y equals 8?

First you need to solve for y like this: 6x+3y=8 3y=-6x+8 y=-2x+8/3 Once you have the equation solved for y, the coefficient of x equals the slope: slope = -2

How would you solve y squared equals 11y?

y*y = 11y Divide both sides by y: y = 11

Y equals 6x-16 y equals -2x plus 8?

y=6x-16 y=-2x+8

What is the slope-intercept form of -6x plus y equals 9?

-6x + y = 9 (+6x) -> y = 6x + 9

People also asked